2016
DOI: 10.3390/ijms17091492
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Virulence-Associated Genes Using Transcriptomic and Proteomic Association Analyses of the Plant Parasitic Nematode Bursaphelenchus mucronatus

Abstract: Bursaphelenchus mucronatus (B. mucronatus) isolates that originate from different regions may vary in their virulence, but their virulence-associated genes and proteins are poorly understood. Thus, we conducted an integrated study coupling RNA-Seq and isobaric tags for relative and absolute quantitation (iTRAQ) to analyse transcriptomic and proteomic data of highly and weakly virulent B. mucronatus isolates during the pathogenic processes. Approximately 40,000 annotated unigenes and 5000 proteins were gained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
(91 reference statements)
2
10
0
Order By: Relevance
“…The FAR protein accelerates the absorption and transportation of fatty acids and retinoids, helping nematodes to infect the host and inhibit the host defenses ( Basavaraju et al, 2003 ). Previous reports demonstrated that FAR expression increased when the nematodes infected and colonized host trees ( Cheng et al, 2013 ; Zhou L. et al, 2016 ). Employing the most suitable gene combination ( TUB / 18S rRNA / UBCE ) to normalize FAR expression under the two habitat conditions, we were able to demonstrate that the expression of the gene significantly increased when the nematodes were inoculated into pine trees.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The FAR protein accelerates the absorption and transportation of fatty acids and retinoids, helping nematodes to infect the host and inhibit the host defenses ( Basavaraju et al, 2003 ). Previous reports demonstrated that FAR expression increased when the nematodes infected and colonized host trees ( Cheng et al, 2013 ; Zhou L. et al, 2016 ). Employing the most suitable gene combination ( TUB / 18S rRNA / UBCE ) to normalize FAR expression under the two habitat conditions, we were able to demonstrate that the expression of the gene significantly increased when the nematodes were inoculated into pine trees.…”
Section: Discussionmentioning
confidence: 95%
“…Eight candidate reference genes were selected which had previously been reported to be suited to transcript normalization in other organisms under different experimental conditions. The sequences of candidate reference genes were obtained from the transcriptome de novo assembly sequences of B. mucronatus ( Zhou L. et al, 2016 ). Primers were designed using Primer Premier 5 software (Premier Biosoft International, Palo Alto, CA, United States), according to the SYBR Green Master Mix (Vazyme, Nanjing, China) manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, our results are in accord with the large number of previous studies that employed the J2 for RNAi. [40][41][42] Small body size genes (sma) were firstly identified in Sydney Brenner's classic screen by the relative decrease of nematode body size in C. elegans. 43 Subsequently, the much more direct way, genetic screen was exploited for isolation of sma.…”
Section: Wileyonlinelibrarycom/journal/psmentioning
confidence: 99%
“…Many studies have been carried out to find ways to diagnose and block PWD, and most of them have been focused on B. xylophilus and its beetle vectors 911 . Currently, to diagnose PWD, B. xylophilus or DNA fragments from B. xylophilus must be detected in tree samples 12 , or PWD symptoms must be observed.…”
Section: Introductionmentioning
confidence: 99%